The Use of the Digital Supply Chain Tool in the Real Sector of the Economy - A.V. Kolesnikov; I.R. Zaripova; E. Kamchatova; Yu. Iu.V. Panko; R.V Kamanina (International Journal of Supply Chain Management, 2020)
Abstract— As everyone knows, the developed countries of the world are quite actively using digital technologies in their supply chain system. Thanks to the rise of technology, supply chain is also becoming more visible. It has allowed for data transparency to expand and thus, affecting the way organizations have the ability to gain visibility on real-time issues about their supply chain networks. This combination has made it possible for supply chain to become more powerful and accessible. The changes in demands and economy along with the rise of technology has made all the difference. This expansion is driving change for faster results and flow, thus the rise of digitalization has become a major contributor of the supply chain market. Based on the available data, we can say that the main share of digital technologies in the developed world is used in the supply chain sector. However, over the past 10 years, digital technologies have also begun to be used in strategically important sectors of the economy, such as the production, processing and sale of products. Moreover, the level of digitalization of some technological supply chain processes reaches 80% or higher. In Russian practice, there are a number of legal acts that promote the development of digital technologies in the real sector of the economy. In addition, the directions and even measures of state support are outlined. This article describes the authors’ vision of the state of digitalization in the agro-industrial complex of Russia, the problems that exist, areas of improvement, risks and threats that authorities and commercial organizations will face when implementing digital technologies. Based on world practice, the study provides data indicating the positive role of digital technologies: increasing the profitability of production, saving costs, increasing production indicators. The study shows the main breakthrough technological platforms on which the development of digital technologies in agricultural production will be based.